Factors associated with the severity of COVID‐19 outcomes in people with neuromuscular diseases: Data from the International Neuromuscular COVID‐19 Registry. (18th November 2022) - Pizzamiglio, Chiara; Pitceathly, Robert D. S.; Lunn, Michael P.; Brady, Stefen; De Marchi, Fabiola; Galan, Lucia; Heckmann, Jeannine M.; Horga, Alejandro; Molnar, Maria J.; Oliveira, Acary S. B.; Pinto, Wladimir B. V. R.; Primiano, Guido; et al.
Abstract: Background and purpose: Clinical outcome information on patients with neuromuscular diseases (NMDs) who have been infected with SARS‐CoV‐2 is limited. The aim of this study was to determine factors associated with the severity of COVID‐19 outcomes in people with NMDs. Methods: Cases of NMD, of any age, and confirmed/presumptive COVID‐19, submitted to the International Neuromuscular COVID‐19 Registry up to 31 December 2021, were included. A mutually exclusive ordinal COVID‐19 severity scale was defined as follows: (1) no hospitalization; (2) hospitalization without oxygenation; (3) hospitalization with ventilation/oxygenation; and (4) death. Multivariable ordinal logistic regression analyses were used to estimate odds ratios (ORs) for severe outcome, adjusting for age, sex, race/ethnicity, NMD, comorbidities, baseline functional status (modified Rankin scale [mRS]), use of immunosuppressive/immunomodulatory medication, and pandemic calendar period. Results: Of 315 patients from 13 countries (mean age 50.3 [±17.7] years, 154 [48.9%] female), 175 (55.5%) were not hospitalized, 27 (8.6%) were hospitalized without supplemental oxygen, 91 (28.9%) were hospitalized with ventilation/supplemental oxygen, and 22 (7%) died. Higher odds of severe COVID‐19 outcomes were observed for: age ≥50 years (50–64 years: OR 2.4, 95% confidence interval [CI] 1.33–4.31; >64 years: OR 4.16, 95% CI 2.12–8.15; both vs. <50 years); non‐White race/ethnicity (OR 1.81, 95% CI 1.07–3.06; vs. White); mRS moderately severe/severe disability (OR 3.02, 95% CI 1.6–5.69; vs. no/slight/moderate disability); history of respiratory dysfunction (OR 3.16, 95% CI 1.79–5.58); obesity (OR 2.24, 95% CI 1.18–4.25); ≥3 comorbidities (OR 3.2, 95% CI 1.76–5.83; vs. ≤2; if comorbidity count used instead of specific comorbidities); glucocorticoid treatment (OR 2.33, 95% CI 1.14–4.78); and Guillain–Barré syndrome (OR 3.1, 95% CI 1.35–7.13; vs. mitochondrial disease). Conclusions: Among people with NMDs, there is a differential risk of COVID‐19 outcomes according to demographic and clinical characteristics. These findings could be used to develop tailored management strategies and evidence‐based recommendations for NMD patients.